"Following Anne Lister: Continuity and queer history before and after the late nineteenth century". Issue 4 (18th November 2022) - Upchurch, Charles
Abstract: This article addresses the question of whether Anne Lister can be considered a lesbian through a reassessment of how the modern period is conceptualized within the history of sexuality. Returning to the original texts that first defined the history of sexuality project, the article emphasized that those texts indicate that the mechanisms of biopower and identity formation based on cultural texts undergo their most significant shift in the late seventeenth and early eighteenth centuries, rather than in the late nineteenth. The formation of sexuality as a disciplinary mechanism, and identities based on it, originated in the late nineteenth century, but many of the mechanisms through which this occurred were in operation earlier. Much of what is now known about gender and sexuality in the eighteenth and early nineteenth centuries was unknown at the time that the history of sexuality project was first formulated, leading to a starker divide being drawn between the late nineteenth century and earlier periods than is warranted. This article argues that the example of Anne Lister can lead to a better appreciation of the continuities in how cultural texts shaped understandings of desire from the early eighteenth century forward.